Investment over the Business Cycle: Insights from College Major Choice - Blom, Erica; Cadena, Brian C.; Keys, Benjamin J. (Journal of Labor Economics, 2021)
How does personal exposure to economic conditions affect individual human capital investment choices? Focusing on bachelor’s degree recipients, we find that cohorts exposed to higher unemployment rates during typical schooling years select majors that earn higher wages, have better employment prospects, and lead to work in a related field. Conditional on expected earnings, recessions also encourage women to enter male-dominated fields, and students of both genders pursue more difficult majors. We conclude that economic environments change how students select majors, and we find evidence that students who respond to the business cycle enjoy earnings typical of their new majors.